Enhancing the Quality of the Characteristic Transmittance Curve in the Infrared Region of Range 2.5–7 µm of the Optical Magnesium Fluoride (MgF2) Ceramic Using the Hot-Pressing Technique in a Vacuum Environment - Nguyen Tuan Hieu; Van Thom Do; Nguyen Dinh Thai; Tran Duc Long; Phung Van Minh (Advances in Materials Science and Engineering)
This paper carries out an experimental study to enhance the quality of the characteristic transmittance curve in the infrared range of 2.5–7 µm of the optical magnesium fluoride (MgF2) ceramic. This work evaluates the effectiveness of using vacuum environment in the MgF2 ceramic hot-pressing technique by comparing the density and the quality of the transmittance characteristic curve of two types of specimens manufactured by the hot-pressing technique corresponding to open air and vacuum environment under the same technological parameters including temperature 650°C, time 30 min, and pressure 200 MPa. The results present that, in comparison with using the hot-pressing technique in the open air, when using the hot-pressing technique in a vacuum environment, the transmittance increases about 4–10%, the characteristic transmittance curve is smoother and has fewer peak points, and the wide of peak points are smaller. When hot-pressing in a vacuum environment, the temperature can be up to 750°C in order to obtain the magnesium fluoride (MgF2) ceramic with the highest quality of characteristic line in the infrared range of 2.5–7 µm. Seventeen specimens are manufactured to conduct the experimental study in order to figure out the optimal set of technological parameters (temperature T = 640.9°C, time t = 33.0 min, and pressure P=231.4 MPa) when hot-pressing in a vacuum environment by the experimental planning approach.